Digital Model for Procurement Management in Thai Supply Chain - Chansamut, Artaphon (ExcelingTech, 2023)
An aim of the paper is to study and to assess digital model for procurement management in Thai supply chain. A samples are ten experts in the field of information and supply chain. The data is analysed by means and standardized deviations. The paper consists of seven elements namely main elements Suppliers , Producer, Finished goods and Customers and Satisfaction. The assessment about digital model in supply chain for the cargo maritime transport management in Thailand using Black-Box technique. The research findings revealed that digital model for procurement management in Thai supply chain is appropriate at the high level , the ten experts agreed.